Description of chromosomal abnormalities in patients bearers of multiple myeloma followed up at the Bone Marrow Transplant Center of the Hospital Portugues in Salvador, Bahia. - Pallotta Filho, Ronald Sérgio; Mello, Mônica Conchon Ribeiro de (Brazilian Journal of Transplantation, 2009)
In recent years, there has been a revolution in the knowledge concerning the pathogenesis of multiple myeloma. The incorporation of cytogenetics and molecular biology has allowed the determination of chromosomal changes sometimes related to different subgroups of the disease, contributing as biological markers of prognosis and for making clinical decisions Purpose: To describe the chromosomal abnormalities in patients with multiple myeloma at the Bone Marrow Transplant Center of the Hospital Portugues in Salvador, Bahia. Methods: A cross-section descriptive study from medical records of patients with multiple myeloma followed from 2001 to 2006 at the Center, who routinely as part of the diagnostic procedures and/or along the treatment had the disease assessed by the bone marrow collec- tion for cytogenetic, histological and immunohistochemical analysis to assess the involvement of the site. Results: From 39 patients able to be analyzed, in 51% of cases there were no metaphases, in 36% were observed no abnormal karyotype, and in 13% was found changes. Correlation between viability of the cytogenetic analysis and rate of active disease in patients showed a prevalence as much as 1.8, while the correlation between cytogenetic changes in patients with active disease, the prevalence rate was 5.5. Conclusion: Therefore, despite the low mitotic index of the disease, the authors confirmed that cytogenetic is an appropriate tool to set the prognosis, especially when performed in patients with active disease, and this should be part of the initial study of patients with multiple myleloma, and it may help the therapeutic strategy to be defined.